Students' Scientific Ability through Contextual Scientific-based Learning Tools During Covid-19 Outbreak - Andriana, Encep; Yuliana, Rina; Setiawan, Sigit; Noviyanti, Tri Esti; Ulfahmi, Krisdiana Indri; Evasufi, Laksmi; Fajari, Widi (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to find out how students 'scientific abilities are using contextual scientific-based learning tools during the Covid 19 pandemic. The method used in this research is descriptive quantitative. This research was conducted by conducting structured observations and questionnaires. In the data collection process, the researcher conducted three different ways of collecting data: the door-to-door system, the home visit system, and conventional learning. The results of students' scientific abilities using contextual scientific-based learning tools with door-to-door data retrieval systems of 81.56%, which are included in the very good category, in the home visit data collection system of 84.06% which are included in the very good category and the system data collection of conventional learning in class by 88% which is included in the very good category. Based on the study's results, it can be concluded that contextual scientific-based learning tools can be very well used in science learning after going through 3 different ways: the door-to-door system, the home visit system, and the conventional one.